A Research on Ethnography of Communication: Ujuban in Tahlilan in Moslem Community in Tawang Village - Moch Yusuf Zen (Asketik : Jurnal Agama dan Perubahan Sosial, 2019)
This is a qualitative research with the objectives are to reveal the meanings behind Ujuban in Tahlilan and factors involved in preserving Ujuban in Tahlilan in Moslem community in Tawang village, Kediri Regency. This research is ethnography of communication with Hymes’ SPEAKING model for analyzing the data. It was collected by observing, depth interviews, participating in group activities, and testing the validity of the data by using data triangulation. After five-month research, the result shows that Ujuban in Tahlilan has deep philosophy meanings as reflections of death. It also proves that factors of beliefs and socio-cultures bond the community to preserve Ujuban in Tahlilan in which nowadays, it is very rare. The research proves that religion even has contribution to preserve the local culture descended by their ancestors, by embracing it in a beautiful acculturation.